Poster 245: Periarticular Local Infiltrative Anesthesia after Anterior Cruciate Ligament Reconstruction: A Comparison to Regional Adductor Canal Block with Matched Sub-Analysis. Issue 7 (30th July 2022) - Schaver, Andrew; Glass, Natalie; Duchman, Kyle; Wolf, Brian; Westermann, Robert
Objectives: There is a paucity of literature that directly compares postoperative pain control and hospital recovery after using periarticular local infiltrative anesthesia (LIA) or regional anesthesia with an adductor canal block (ACB) for ambulatory anterior cruciate ligament reconstruction (ACLR) surgery. Additional studies are needed to investigate the analgesic efficacy of both ACB and LIA in patients undergoing ACLR surgery with concomitant procedures. The purpose of this study is to compare postoperative pain and recovery after anterior cruciate ligament reconstruction (ACLR) in patients who received an adductor canal block (ACB) or periarticular local infiltrative anesthesia (LIA). Methods: Study Design: Retrospective comparison studyA retrospective review of a prospectively collected ACL registry was performed. Patients underwent ACLR at a single institution between January 2015 and September 2020 and received long-acting local anesthesia with a pre-operative ultrasound-guided ACB or peri-articular LIA after surgery. Visual Analog Scale (VAS) pain scores, milligram morphine equivalents (MME) consumed in the post-anesthesia care unit (PACU), and total hospital recovery time were compared. Univariate analysis was used to compare VAS pain and MME totals between overall groups and groups matched for age, sex, BMI, graft type, and meniscal treatment. A p-value < 0.05 indicated statistical significance. Results: There were 265 knees (253 patients) included (LIA, 157 knees; ACB, 108 knees). Overall, VAS pain scores before hospital discharge (LIA 2.6 ± 1.5 vs. ACB 2.4 ± 1.4, p=0.334) and total MMEs were similar (LIA 17.6 ± 7.6 vs. ACB 18.5 ± 6.7 (MME), p=0.134). Total time to discharge also did not significantly differ (LIA 137.5 (IQR:116-178) vs. ACB 147 (IQR:123-183) (min), p=0.118). Matched sub-analysis (LIA and ACB, n=94) did not reveal significant differences in VAS pain before discharge (LIA 2.4 ± 1.4 vs ACB: 2.7 ± 1.5, p=0.122) or total MMEs (LIA 18.6 ± 6.7 vs. ACB 17.9 ± 7.1, p=0.532). Conclusions: The use of ACB or LIA resulted in similar pain levels and opioid consumption during early recovery after ACLR surgery.